2021
DOI: 10.3390/toxins13080553
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis Cry4Ba Insecticidal ToxinExploits Leu615 in Its C-Terminal Domain to Interact with a Target Receptor—Aedes aegypti Membrane-Bound Alkaline Phosphatase

Abstract: In addition to the receptor-binding domain (DII), the C-terminal domain (DIII) of three-domain Cry insecticidal d-endotoxins from Bacillus thuringiensis has been implicated in target insect specificity, yet its precise mechanistic role remains unclear. Here, the 21kDa high-purity isolated DIII fragment derived from the Cry4Ba mosquito-specific toxin was achieved via optimized preparative FPLC, allowing direct rendering analyses for binding characteristics toward its target receptor—Aedes aegypti membrane-bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 63 publications
(93 reference statements)
2
17
0
Order By: Relevance
“…The docking result showed that the major domain II residues that function in binding to the Aa-mALP receptor are on a side surface rather than only as residues on the beta-hairpin loops located on the underside of the toxin. In our previous work, some binding residues from this docking result were studied and we found that Leu 615 in the β22–β23 loop of the Cry4Ba domain III toxin was a crucial residue for Aa-mALP receptor binding [ 21 ]. In the present study, aromatic and hydrophobic residues of Cry4Ba domain II (Trp 327 , Tyr 347 , Ile 358 , and Tyr 359 ) and domain III (Phe 490 and Leu 517 ) and their counterpart interacting residues (Gly 513 , Ser 490 , His 500, Phe 497 , Leu 53 , and Leu 52 , respectively) on Aa-mALP ( Figure 1 ) predicted as responsible for binding were selected to study their relevance to binding and toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The docking result showed that the major domain II residues that function in binding to the Aa-mALP receptor are on a side surface rather than only as residues on the beta-hairpin loops located on the underside of the toxin. In our previous work, some binding residues from this docking result were studied and we found that Leu 615 in the β22–β23 loop of the Cry4Ba domain III toxin was a crucial residue for Aa-mALP receptor binding [ 21 ]. In the present study, aromatic and hydrophobic residues of Cry4Ba domain II (Trp 327 , Tyr 347 , Ile 358 , and Tyr 359 ) and domain III (Phe 490 and Leu 517 ) and their counterpart interacting residues (Gly 513 , Ser 490 , His 500, Phe 497 , Leu 53 , and Leu 52 , respectively) on Aa-mALP ( Figure 1 ) predicted as responsible for binding were selected to study their relevance to binding and toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…For the Cry4Ba toxin, several amino acid residues on β-hairpin loops, especially those located on the lower part of domain II such as Thr 386 , Ser 387 , Ser 388 , Pro 389 , Ser 390 , and Asn 391 on the β6–β7 loop, Glu 417 on the β8–β9 loop, and Tyr 455 and Asn 456 on the β10–β11 loop, have been reported to be important for binding and toxicity [ 16 , 22 ]. Our previous study [ 21 ], using molecular docking, revealed a possible Cry4Ba toxin—Aa-mALP receptor interaction in which surface residues on the side of the domain II, such as residues on β2 and β4 and residues on the β-hairpin loops of domains II and III rather than only the residues on the β-hairpin loops at the bottom of domain II, are responsible for binding to the Aa-mALP receptor ( Figure 1 ). According to a previous study, three fundamental hotspot residues (tryptophane, tyrosine, and arginine) were reported to contribute more significantly to binding affinity in protein–protein interfaces compared with others (for review, see [ 27 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While various studies have suggested that the C-terminal domain—DIII could be implicated in preserving structural integrity or in determining target insect specificity [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], we have recently revealed that Cry4Ba-DIII could function as a tight-binding anchor for lipid membrane bilayers, highlighting its potential contribution to toxin-membrane interactions to mediate toxin activity [ 34 ]. More recently, we have demonstrated that Cry4Ba-DIII could also act as a receptor-binding moiety, signifying another contribution to toxin interactions with its target protein receptor— Aa -mALP in mediating larval toxicity [ 35 ].…”
Section: Introductionmentioning
confidence: 99%